2005
DOI: 10.1097/00041444-200503000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Association study of 90 candidate gene polymorphisms in panic disorder

Abstract: The study results suggest that genetic variants of several candidate genes of neurotransmitter systems, each of a minor individual effect, may contribute to the susceptibility to PD. Our data also indicate that genetic variability may have a distinctive influence on pure and comorbid phenotypes of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 58 publications
3
71
2
Order By: Relevance
“…Our study also showed a significant association with the 5-HT2A receptor 102T-C polymorphism in pure, but not in comorbid, PD (Maron et al, 2005b). Both studies showed that the 102C allele was more frequent among patients, suggesting a significant role for this allele in the predisposition to PD.…”
Section: -Ht Receptor Genessupporting
confidence: 71%
See 4 more Smart Citations
“…Our study also showed a significant association with the 5-HT2A receptor 102T-C polymorphism in pure, but not in comorbid, PD (Maron et al, 2005b). Both studies showed that the 102C allele was more frequent among patients, suggesting a significant role for this allele in the predisposition to PD.…”
Section: -Ht Receptor Genessupporting
confidence: 71%
“…A recent study by Rothe et al (2004a) showed an association between the -1019C-G polymorphism and PD with agoraphobia, but no association among the total sample of PD patients. Our study demonstrated a suggestive association of this SNP with PD phenotype (Maron et al, 2005b). Of note, Rothe et al (2004a) showed a significant association with the G allele, whereas our results revealed an association with the C allele.…”
Section: -Ht Receptor Genessupporting
confidence: 44%
See 3 more Smart Citations